Utility of unique optical properties of Anethum graveolens green synthesized mediated-alumina nanoparticles for spectrofluorometric determination of darifenacin in pharmaceutical products - Seham S. Alterary; Gamal A. E. Mostafa; Maha F. El-Tohamy; Haitham AlRabiah (Scientific Reports)
Abstract In this study, a new fluorescence-based analytical method for the determination of darifenacin (DFN) in pharmaceutical formulations using alumina nanoparticles (NPs) and sodium dodecyl sulfate (SDS) is presented. The alumina NPs were synthesized by a green method using Anethum graveolens (extract as a reducing and stabilizing agent. The NPs were characterized by UV-vis spectroscopy, X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and Fourier transform infrared spectroscopy (FTIR). The method enhanced the fluorescence of alumina NPs in the presence of SDS, which stabilized the particles and maintained their dispersion. DFN interacts with the NPs, enhancing fluorescence emission and allowing sensitive detection at λex/λem (290/400 nm). The method quantifies DFN over a concentration range of 0.1–10 µg/mL, with a limit of detection of 0.013 µg/mL and a limit of quantification of 0.043 µg/mL. The recovery percent is over 99%, which demonstrates the accuracy of the method. In accordance with established methodological guidelines, mean precision was used to accurately assess the precision of the results. This fluorescence-based technique offers several key advantages, including rapid analysis, minimal sample preparation, and high specificity, making it a promising tool for routine quality control and pharmaceutical analysis.